Proteomic Analysis of Hippocampus and Cortex in Streptozotocin-Induced Diabetic Model Mice Showing Dementia - Kenji Matsuura; Mieko Otani; Masaoki Takano; Keiichi Kadoyama; Shogo Matsuyama (Journal of Diabetes Research)
Aim. Diabetes with its associated hyperglycemia induces various type of peripheral damage and also impairs the central nervous system (CNS). This study is aimed at clarifying the precise mechanism of diabetes-induced dementia as an impairment of CNS. Methods. The proteomic analysis of the hippocampus and cortex in streptozotocin- (STZ-) treated mouse diabetic model showing dementia was performed using two-dimensional gel electrophoresis (2-DE) followed by mass spectrometry (n=3/group). Results. Significant changes in the expression of 32 proteins and 7 phosphoproteins were observed in the hippocampus and cortex. These identified proteins and phosphoproteins could be functionally classified as cytoskeletal protein, oxidoreductase, protein deubiquitination, energy metabolism, GTPase activation, heme binding, hydrolase, iron storage, neurotransmitter release, protease inhibitor, transcription, glycolysis, antiapoptosis, calcium ion binding, heme metabolic process, protein degradation, vesicular transport, and unknown in the hippocampus or cortex. Additionally, Western blotting validated the changes in translationally controlled tumor protein, ATP-specific succinyl-CoA synthetase beta subunit, and gamma-enolase isoform 1. Conclusions. These findings showed that STZ-induced diabetes changed the expression of proteins and phosphoproteins in the hippocampus and cortex. We propose that alterations in expression levels of these proteins play an important role in diabetes-induced dementia.